Simultaneous detection of endogenous lectins and their binding capacity at the single-cell level--a technical note - Fronková, V; Holíková, Z; Liu, F T; Homolka, J; Rijken, D C; André, S; Bovin, N V; Smetana, K; Gabius, H J (Folia biologica, 1999)
Endogenous lectins are proteins/glycoproteins which selectively recognize distinct saccharide ligands and are different from immunoglobulins and carbohydrate-utilizing enzymes. Expression of these molecules can be detected immunohistochemically using nonblocking monoclonal antibodies (A1D6: anti-galectin-3, MR-15-2-2: anti-175 kD mannose receptor). Alternatively, biotinylated (neo)glycoconjugates which are recognized by a studied lectin can be employed as convenient probes to demonstrate specific binding of sugar epitopes by carbohydrate recognition domains (CRD) of endogenous lectins. In this study, we describe a new procedure for immunocytochemical visualization of the expression of endogenous lectins and glycochemical visualization of the reactivity of carbohydrate recognition domain(s), performed simultaneously at the single-cell level.
Keywords: Mannose Receptor; lektiny typu C; Ligands; Oligosaccharides; Epitopes; Humans; ligandy; glykokonjugáty; Galectin 3; lektiny vázající mannosu; receptor mannózy; Immunoenzyme Techniques; Antibodies, Monoclonal; lektiny; krysa rodu Rattus; Biotinylation; Lectins, C-Type; lidé; zvířata; diferenciační antigeny; receptory buněčného povrchu; imunoenzymatické techniky; Lectins; Mannose-Binding Lectins; biotinylace; Receptors, Cell Surface; obrovské buňky; Receptors, Mitogen; Macrophages, Alveolar; galektin 3; oligosacharidy; monoklonální protilátky; Antigens, Differentiation; Rats; Glycoconjugates; Animals; Giant Cells; epitopy; receptory mitogenů; alveolární makrofágy